P33 Real- world data from a tertiary liver centre for patients with chronic liver disease receiving palliative care. (28th September 2020) - Halim, Amir; Panagaris, Theodoros; Hogan, Brian; Prentice, Wendy
Abstract : Despite the increasing number of patients dying from chronic liver disease (CLD) globally, involvement of palliative services remains a distinct challenge in this cohort. This study evaluated the level of palliative care CLD patients, managed in a tertiary liver centre, received. Data was collected retrospectively for patients who died in hospital between May 2015–2018. A list was obtained from the coding department and filtered to identify only the patients that died during their admission. The clinical notes for each patient were scrutinised using the hospital's electronic database. Only patients with CLD who had regular follow up at the centre were included in the study. Patients that were admitted to an intensive care unit, listed for liver transplant, referred from another trust, first presentation CLD, not previously known to the hospital, admitted for pre- transplant assessment, or where cause of death was unrelated to CLD, were excluded from the study. 3003 CLD patients required 6088 admissions between May 2015–2018. There were 350 deaths. 28 patients were identified following application of the inclusion criteria. The patients had an average of six unplanned hospital visits in the last 12 months of life. The average length of their last admission was 18 days. Patients were referred to the palliative care team an average of six days prior to death and an average of 10 days after admission. 29% were referred to the palliative care team prior to their last admission (Mean = 3 months). Palliative medications were prescribed an average of three days prior to death. 7% had no palliative medications prescribed prior to death. 46% did not have non- essential medications stopped prior to death. 36% continued to have active observations up to death. All patients received regular mouth care. This study has highlighted that most CLD patients receive minimal palliative therapy until the last days of life. CLD runs a protracted, unpredictable course but an increased frequency of hospital admissions appears to a be good indicator of disease terminality. Predicting reversibility of decompensation in CLD is challenging even for experienced clinicians. As a result, most clinicians remain reluctant to offer palliation until the last days of life. Earlier engagement with palliative care would help patients and relatives accept their prognosis and establish treatment limits. It is unlikely to reduce the number of hospital admissions; however, it is more likely to help patients attain better symptom control and avoid unnecessary medical treatment.